2020
DOI: 10.1159/000509147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substance Misuse and Family History of Substance Use Disorder on Delay Discounting in Adolescents and Young Adults with Attention-Deficit/Hyperactivity Disorder

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) and substance use disorder (SUD) often co-occur. Both disorders are characterized by impulsive choice. However, little is known about the effects of substance misuse (SM) and family history of SUD (FH) on impulsive choice in ADHD-SUD comorbidity. Impulsive choice is also linked to callous-unemotional (CU) traits, which are suggested to play a role in ADHD-SUD comorbidity. Our aim was to examine the effects of (1) FH and (2) SM on impulsive choice, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(73 reference statements)
2
2
0
Order By: Relevance
“…The study found no evidence supporting any differences in performance on tasks of DA, risk adjustment and reflection impulsivity between the ADHD only group and HC. This is in accordance with the findings of two previous studies [ 5 , 15 ], demonstrating impairments in impulsive choice, operationalized as DD, between CUD/ADHD, and substance misuse + ADHD, but not between ADHD only and HC. However, the current cross-sectional design does not allow for inference about the nature of this relationship.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study found no evidence supporting any differences in performance on tasks of DA, risk adjustment and reflection impulsivity between the ADHD only group and HC. This is in accordance with the findings of two previous studies [ 5 , 15 ], demonstrating impairments in impulsive choice, operationalized as DD, between CUD/ADHD, and substance misuse + ADHD, but not between ADHD only and HC. However, the current cross-sectional design does not allow for inference about the nature of this relationship.…”
Section: Discussionsupporting
confidence: 93%
“…One study found steeper DD in individuals with comorbid cocaine use disorder (CUD) and ADHD, compared to individuals with ADHD only [ 5 ]. This is consistent with findings in two recent studies investigating comorbid individuals with ADHD, substance misuse and cannabis use disorders, respectively [ 15 , 16 ]. Similarly, another study found steeper DD in comorbid CUD/ADHD compared to individuals with CUD only [ 17 ].…”
Section: Introductionsupporting
confidence: 93%
“…Both ADHD and SUDs are characterized by choice impulsivity [ 180 ]. There are recent data to support the possibility that choice impulsivity in ADHD results from substance misuse [ 181 ]. A popular explanation for the association between ADHD and EDs is that impulsive behavior generates the disordered eating [ 182 , 183 ].…”
Section: Other Psychiatric Diagnosesmentioning
confidence: 99%
“…[ 21 ] Previous studies show that ADHD is associated with several risks and related factors. Some related factors including marital divorce,[ 22 ] living with single parents,[ 23 ] fathers’ education,[ 24 ] family history, order of birth,[ 25 ] rural residency,[ 26 ] parental smoking,[ 21 27 ] childhood medical history, and some risk factors such as birth weight, maternal tobacco use,[ 28 ] and history of psychological problems in the family. [ 24 25 29 ]…”
Section: Introductionmentioning
confidence: 99%